The experience of witnesses who testified at the Truth and Reconciliation Commission: testimonial process and psychological healing in the aftermath of trauma - Mohamed, Ahmed-Riaz (Department of Psychology, 2015)
The aim of the study was to examine the relationship between the experience of testifying before the TRC among victims and survivors of gross human rights abuses, and the objectives that were set out by the TRC with regard to healing.